2017
DOI: 10.3905/jpm.2017.43.4.112
|View full text |Cite
|
Sign up to set email alerts
|

The Diversification Delta: A Different Perspective

Abstract: In a 2012 article published in this Journal, Vermorken, Medda, and Schröder introduce a new measure of diversification, the Diversification Delta (DD), based on the entropy of the portfolio return distribution. Entropy as a measure of uncertainty has been used successfully in several frameworks and takes into account the entire statistical distribution rather than just the first two moments. In this article, the authors highlight some drawbacks of the DD measure and go on to propose an alternative measure base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Resilience engineering aims to plan systems that exhibit respective characteristics, with the robustness of networks, independent of their scale, being the goal [103,105]. This scientific realm provides metrics and modeling frameworks to design system reliability: for example, in the anticipation of individual supply chain shocks [100,101], chemical process systems engineering [106], classical flexibility analysis [107], management of portfolios [108,109], and food webs and economic networks [110].…”
Section: Reliability Actionsmentioning
confidence: 99%
“…Resilience engineering aims to plan systems that exhibit respective characteristics, with the robustness of networks, independent of their scale, being the goal [103,105]. This scientific realm provides metrics and modeling frameworks to design system reliability: for example, in the anticipation of individual supply chain shocks [100,101], chemical process systems engineering [106], classical flexibility analysis [107], management of portfolios [108,109], and food webs and economic networks [110].…”
Section: Reliability Actionsmentioning
confidence: 99%
“…Key papers on this topic are Markowitz (1952) and more recently Booth and Fama (1992), Chua et al (2009), Choueifaty and Coignard (2008), Kinlaw et al (2021), Rudin and Morgan (2006), Flores et al (2017), andYeung et al (2012), among many others. Choueifaty and Coignard (2008) studied maximum diversification and confirmed that constant proportion portfolios earn additional returns labeled diversification returns by Booth and Fama (1992).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the concept of diversification in general and correlation diversification in particular is misunderstood as revealed by the 2007-2009 financial crisis (Ilmanen and Kizer 2012;Miccolis and Goodman 2012;Statman 2013). An example of an inadequate correlation diversification measure is diversification delta, which was introduced by Vermorken et al (2012) and revised by Salazar Flores et al (2017).…”
Section: Introductionmentioning
confidence: 99%